« Il y aurait peut-être lieu de lui donner une chance […]. C’est une aventure de jeunesse ». Les délinquants juvéniles devant la Cour de Bien-être social de Chicoutimi (Québec) de 1963 à 1967 - Catherine Tremblay (Criminocorpus)
This article proposes to observe the voice of juvenile delinquents through the various stages of the judicial process that can be deployed at the Court of Social Welfare of Chicoutimi, (Quebec) from 1963 to 1967. The protective approach endorsed by this court was aim of ensuring the well-being and rehabilitation of juvenile offenders. Following these principles, the court examines the multiple dimensions of the child's life through various processes. This article, by observing the investigations carried out by various experts (judges, probation officers, psychologists, psychiatrists, etc.), proposes that the voice of the delinquent minor knows a very variable reception and that according to the objectives of the interlocutor who receives it.